2023
DOI: 10.1111/jors.12632
|View full text |Cite
|
Sign up to set email alerts
|

Rationality test in the housing market: Project‐level evidence from China

Abstract: We test whether investors rationally react to rent news when pricing houses. Previous literature on house pricing uses aggregated housing price and rent data to estimate the rent news. We analytically demonstrate that using aggregated data biases the rationality test because it forces researchers to estimate the rent news using the crossproject average dynamic relationship among the housing return, rent growth, and macroeconomic dynamics and, hence, misses the heterogeneity in the dynamic relationship. Our emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Individuals' entry into the housing market as investors increase by 20% if they have recently moved or if their neighbour has started investing in property (Bayer, et al, 2016). Chen et al (2021) provide evidence of speculators' impact on feedback or momentum trading in the housing market. They found that short-term speculators contribute to price overreactions in shallow markets with limited price information.…”
Section: Housing Market Investor Typesmentioning
confidence: 91%
“…Individuals' entry into the housing market as investors increase by 20% if they have recently moved or if their neighbour has started investing in property (Bayer, et al, 2016). Chen et al (2021) provide evidence of speculators' impact on feedback or momentum trading in the housing market. They found that short-term speculators contribute to price overreactions in shallow markets with limited price information.…”
Section: Housing Market Investor Typesmentioning
confidence: 91%